2018
DOI: 10.1007/jhep11(2018)068
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of multiparticle scattering in λϕ4 theory

Abstract: We study numerically classical collisions of waves in λφ 4 theory. These processes correspond to multiparticle scattering in the semiclassical regime. Parameterizing initial and final wavepackets by energy E and particle numbers N i , N f we find classically allowed region in the parameter space. We describe properties of the scattering solutions at the boundary of the classically allowed region. We comment on the implications of our results for multiparticle production in the quantum regime.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 52 publications
3
8
0
Order By: Relevance
“…For a recent review of semiclassical techniques for multiparticle production see[12] 2. Recently the authors of[13] have used classical simulations to study high multiplicity processes 3. For a discussion on the nature of the underlying quantum field theory, in particular, on aspects of localizability and unitarity in a theory featuring "Higgsplosion" see[25][26][27].…”
mentioning
confidence: 99%
“…For a recent review of semiclassical techniques for multiparticle production see[12] 2. Recently the authors of[13] have used classical simulations to study high multiplicity processes 3. For a discussion on the nature of the underlying quantum field theory, in particular, on aspects of localizability and unitarity in a theory featuring "Higgsplosion" see[25][26][27].…”
mentioning
confidence: 99%
“…To generate such ensemble we use Metropolis Monte Carlo algorithm and vary values of β and ξ to reach the boundary of classically allowed solution in the parameter space (Ẽ,Ñ f ), see Ref. [11] for details. In the next Section we present obtained results.…”
Section: The Methodsmentioning
confidence: 99%
“…In the opposite case such a process belongs to classically forbidden region and its probability is expected to be suppressed exponentially. In this talk we report numerical results [11] on classical scattering of wave packets in λφ 4 theory.…”
Section: Introductionmentioning
confidence: 99%
“…A considerable revival of the interest in multiparticle processes occurred recently [6][7][8][9][10][11] when Ref. [12] suggested that, contrary to Eq.…”
Section: Introductionmentioning
confidence: 99%
“…( 1), the cross section of multiple Higgs boson production grows factorially at high energies. This "Higgsplosion" mechanism was subsequently criticised in [8,[13][14][15], so that now the situation is far from being settled. It is clear that further development of reliable methods for the calculation of multiparticle amplitudes is required.…”
Section: Introductionmentioning
confidence: 99%